ISLAM AND THE HUMANITY OF THE STATE: From Fiqh of Politics to Fiqh of Citizenship - Prihantoro, Hijrian A. (ULUL ALBAB Jurnal Studi Islam, 2019)
The intellectual debate of this age in the field of Islamic studies is the discovery of the relationship of religion and the nation-state. Religion in the old age is understood by fiqh (Islamic jurisprudence), then the theory of religion on the concept of politics was called the doctrine of fiqh’s politics. The present age shows that the religious man does not speak only about the position of religion in political discourse, but also about the concept of the humanity of the state. I want to apply my study on Islam and humanity of state in the Indonesian context because there are multitudes of nationalities and cultures. This research uses an integrative approach that combines the phenomenological approach with the sociological approach. This research aims to analyze the relation between the religion of Islam and the activity of human thought on the concept of the human state by transforming the concept of the fiqh of politics to the fiqh of citizenship. This research proves that the conceptual transformation from fiqh of politics towards fiqh of citizenship, with all its consequences, must be seen as a process of political agreement and it can be accepted as long as it always pays attention to social justice and general welfare.